High-throughput biochemical profiling reveals functional adaptation of a bacterial Argonaute - Ober-Reynolds, Benjamin; Becker, Winston R; Jouravleva, Karina; Jolly, Samson M; Zamore, Phillip D; Greenleaf, William J (Molecular cell, 2022)
Argonautes are nucleic acid-guided proteins that perform numerous cellular functions across all domains of life. Little is known about how distinct evolutionary pressures have shaped each Argonaute's biophysical properties. We applied high-throughput biochemistry to characterize how Thermus thermophilus Argonaute (TtAgo), a DNA-guided DNA endonuclease, finds, binds, and cleaves its targets. We found that TtAgo uses biophysical adaptations similar to those of eukaryotic Argonautes for rapid association but requires more extensive complementarity to achieve high-affinity target binding. Using these data, we constructed models for TtAgo association rates and equilibrium binding affinities that estimate the nucleic acid- and protein-mediated components of the target interaction energies. Finally, we showed that TtAgo cleavage rates vary widely based on the DNA guide, suggesting that only a subset of guides cleaves targets on physiologically relevant timescales.